2019
DOI: 10.5897/ajar2019.13950
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere yeast Torulaspora globosa with plant growth promotion traits and improvement of the development of tomato seedlings under greenhouse conditions

Abstract: Yeasts are an interesting group of microorganisms, which occur naturally in soil and on plant surfaces. Few studies have analysed their potential as plant growth promoters. Thus, the aim of this study was to evaluate the indole acetic acid (IAA) production and phosphate solubilization by the yeasts Torulaspora globosa (CCA5S51 and CCA5S55), Meyerozyma guilliermondii (CCA3C98), and Rhodotorula mucilaginosa (CCA2F32), and the influence of T. globosa (CCA5S55) in the development of tomato seedlings. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Whether applied individually or in combination, these yeast species have significantly improved both shoot/root dry weight and number of leaves. Moreover, our research has revealed that these extremophilic yeasts possess the ability to enhance nutrient uptake, as evidenced by their increased assimilation of essential nutrients such as N, P, and K. Numerous studies have also substantiated the capacity of yeast strains to promote the growth of Oryza sativa, Solanum lycopersicum , and Nicotiana benthamiana (Amprayn et al 2012 , Thais et al 2019 , Fernandez-San Millan et al 2020 , Tapia-Vázquez et al 2020 ). Fernandez-San Millan et al ( 2020 ) demonstrated the effectiveness of applying R. dairenensis in enhancing the growth and development of Nicotiana benthamiana .…”
Section: Discussionmentioning
confidence: 83%
“…Whether applied individually or in combination, these yeast species have significantly improved both shoot/root dry weight and number of leaves. Moreover, our research has revealed that these extremophilic yeasts possess the ability to enhance nutrient uptake, as evidenced by their increased assimilation of essential nutrients such as N, P, and K. Numerous studies have also substantiated the capacity of yeast strains to promote the growth of Oryza sativa, Solanum lycopersicum , and Nicotiana benthamiana (Amprayn et al 2012 , Thais et al 2019 , Fernandez-San Millan et al 2020 , Tapia-Vázquez et al 2020 ). Fernandez-San Millan et al ( 2020 ) demonstrated the effectiveness of applying R. dairenensis in enhancing the growth and development of Nicotiana benthamiana .…”
Section: Discussionmentioning
confidence: 83%
“…Some studies that show this potential improvement was presented by Liu et al (2016) who managed to improve IAA production by working with Saccharomyces sp. and Torulaspora globosa in YPD media with tryptophan (0.1 % w / v), finding an increase in IAA concentration from 13 mg L -1 to 287 mg L -1 ; and Thais et al (2019) that studied the synthesis of IAA with Torulaspora globosa in supplemented PD media, obtaining a maximum concentration of 669 mg L -1 , values that would have to be carefully analyzed to avoid reaching toxic levels of IAA.…”
Section: Discussionmentioning
confidence: 99%